Speech communication for Filipinos - Concepcion, Proceso G.; De La Cruz, Edna M.;Enriquez, Lina P. (Quezon City, Philippines : Rex Book Store, 1994)
Speech communication for Filipinos is geared to the communication needs of the Filipino. Voice improvement, stress and intonation, the critical vowel and consonant sounds, are given much attention because these are crucial problems of the Filipino communicator in English.
Preface -- I. Essentials of speech -- A. Language and communication -- B. Mechanics of speech -- C. Components of speech -- D. Stress -- E. Intonation -- II. Speech activities for more effective oral communication -- References -- Appendix.
Keywords: SPEECH COMMUNICATION